2020
DOI: 10.3389/fonc.2020.00283
|View full text |Cite
|
Sign up to set email alerts
|

Ephrin-B1 Is a Novel Biomarker of Bladder Cancer Aggressiveness. Studies in Murine Models and in Human Samples

Abstract: Bladder cancer (BC) is the ninth most common cancer worldwide, but molecular changes are still under study. During tumor progression, Epithelial cadherin (E-cadherin) expression is altered and β-catenin may be translocated to the nucleus, where it acts as co-transcription factor of tumor invasion associated genes. This investigation further characterizes E-cadherin and β-catenin associated changes in BC, by combining bioinformatics, an experimental murine cell model (MB49/MB49-I) and human BC samples. In in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…Overexpression of EphB1 promoted the migration and invasion of lung cancer cells [32]. MH Vazquez-Levin and et al found an association between higher EphB1 expression and higher stage and tumor grade of Bladder cancer [33]. ITGB2 encodes integrin subunit β2, which acts like a cancer cell's mechanical anchor to the ECM.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of EphB1 promoted the migration and invasion of lung cancer cells [32]. MH Vazquez-Levin and et al found an association between higher EphB1 expression and higher stage and tumor grade of Bladder cancer [33]. ITGB2 encodes integrin subunit β2, which acts like a cancer cell's mechanical anchor to the ECM.…”
Section: Discussionmentioning
confidence: 99%
“…Ephrin B1 binds to Eph receptor tyrosine kinase and potentiates tumor growth [32]. Ephrin B silencing in invasive MB49 bladder cancer cells (MB49-I) resulted in lower migratory and invasive capacity [33].…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…Substantial evidence indicates that ephrins play a vital role in tumor angiogenesis, invasion, metastasis, and tumor stemness maintenance ( Lodola et al, 2017 ). Many ephrin ligands have been shown to be upregulated in multiple tumors and associated with poor prognosis, such as lung adenocarcinoma ( Deng et al, 2021 ), breast cancer ( Kaenel et al, 2012 ), colorectal cancer ( Papadakos et al, 2022 ), prostate cancer ( Zhao et al, 2021 ), bladder cancer ( Mencucci et al, 2020 ), and other cancers ( Surawska et al, 2004 ). Lin et al (2021) reported that EFNA4 is highly expressed in cancer tissues and leads to poor prognosis in patients with HCC.…”
Section: Introductionmentioning
confidence: 99%